2020
DOI: 10.21203/rs.3.rs-40775/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Favipiravir versus other antiviral or standard of care for COVID-19 treatment: A rapid systematic review and meta-analysis

Abstract: Abstract Background The coronavirus, cause of COVID-19 is an enveloped, RNA virus that utilizes an enzyme RNA dependent RNA polymerase for its replication. Favipiravir (FVP) triphosphate, a purine nucleoside analog, inhibits that enzyme. We have conducted this systematic review and meta-analysis on efficacy and safety of drug FVP as a treatment for COVID-19. Methods Databases like Pubmed, Medline, Google Scholar, preprint sites, and clinicaltirals.gov were searched. S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 7 publications
(7 reference statements)
2
34
1
Order By: Relevance
“…However, this difference was not statistically significant after seven and ten days, which could be related to inappropriate dose and duration of treatment with favipiravir 41 . In another meta-analysis by Shrestha et al, it was stated that viral clearance on seventh and 14 th was not significant between the favipiravir and control groups 40 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this difference was not statistically significant after seven and ten days, which could be related to inappropriate dose and duration of treatment with favipiravir 41 . In another meta-analysis by Shrestha et al, it was stated that viral clearance on seventh and 14 th was not significant between the favipiravir and control groups 40 .…”
Section: Discussionmentioning
confidence: 95%
“…The obtained results demonstrated the clinical improvement after seven and 14 days of hospitalization was more remarkable in patients taking favipiravir than those receiving other drugs. Another meta-analysis conducted by Shrestha et al demonstrated that clinical improvement was observed on both the seventh and 14 th day of treatment 40 . Udwadia et al reported the time of clinical improvement was significantly faster in patients in the favipiravir group than those who are not 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Favipiravir was approved for the treatment of SARS-CoV-2 in Russia and India and currently assessed in many countries. The drug is given orally and improves the patients’ conditions in the clinic compared to the standard of care but no significant difference in viral clearance, the requirement for oxygen support, and side effect profile [ 102 ]. In an open-label clinical trial (ChiCTR2000029600), COVID-19 patients were treated with favipiravir (1600 mg twice daily on Day 1 and 600 mg twice daily on days 2 to 14, orally) or lopinavir-ritonavir (400 mg/100 mg twice daily orally).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Based on these preliminary results, the Russian Ministry of Health granted, in May 2020, a fast-track marketing authorization to favipiravir for the treatment of COVID-19 patients. A meta-analysis of some aforementioned clinical trials showed a significant clinical and radiological improvement with favipiravir compared to the standard of care, but no significant difference with regards to viral clearance, oxygen support requirement, or side effects (Shrestha et al, 2020). Currently, two clinical trials are ongoing to evaluate the efficacy and safety of favipiravir alone (NCT04336904) or in combination with tocilizumab (NCT04310228) for the treatment of COVID-19.…”
Section: Clinical Evidence Of Antiviral Agentsmentioning
confidence: 99%